2010
DOI: 10.1063/1.3327210
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carrier mobility in organic solar cells

Abstract: The microscopic states and performance of organic solar cell are investigated theoretically to explore the effect of the carrier mobility. With Ohmic contacts between the semiconductor and the metal electrodes there are two origins of carriers in the semiconductor: the photocarriers generated by photon absorption and the dark carriers diffused from the electrodes. The power efficiency of the solar cell is limited by the recombination of a carrier with either the photocarrier or a dark carrier. Near the short-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…The influence of mobility on the efficiency and the existence of an optimum mobility have been well discussed in previous studies. [3][4][5][6] From Fig. 3, a higher dielectric constant ε r leads to a higher efficiency, thus a higher peak efficiency.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of mobility on the efficiency and the existence of an optimum mobility have been well discussed in previous studies. [3][4][5][6] From Fig. 3, a higher dielectric constant ε r leads to a higher efficiency, thus a higher peak efficiency.…”
Section: Modelmentioning
confidence: 99%
“…[3][4][5][6][7] It has been shown that there is an optimum value of the mobility that leads to a peak efficiency. [3][4][5][6] Mobilities lower than the optimum value lead to lower efficiencies due to significant reductions in the dissociation rate of polaron pairs into free charge carriers, 3 together with less efficient charge extractions. Mobilities above the optimum value lead to decreases in the open circuit voltage and no significant increase in the dissociation rate of polaron pairs.…”
Section: Introductionmentioning
confidence: 99%
“…This gives a comprehensive picture of the influence of charge carrier mobility, layer thickness, exciton state, and loss mechanisms on the performance of the cell. In addition, it demonstrates how PCE estimation depends on physical parameters (e.g., mobilities [25][26][27]) and the assumptions made for the sub-macroscopic physical processes.…”
Section: Theoretical Background and Modeling Approachmentioning
confidence: 99%
“…In order to determine the optimum mobility for OSC, several theoretical studies drive the impact of mobility on device performance [26,27,[29][30][31][32][33]. Concerning the Langevin theory, charge carrier mobility directly competes with the recombination, where the recombination increased for higher mobility.…”
Section: Loss Mechanism and Mobility Effectmentioning
confidence: 99%
See 1 more Smart Citation